Polarization and Depolarization Current Analysis for Field Degraded Cross Linked Polyethylene Cables - Sulaiman S.; Ariffin A.M.; Kuan T.M.; Osman M.; Nik Ali N.H.; Illias H.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Aliphatic compounds; Depolarization; Deterioration; Dielectric materials; Insulating materials; Insulation; Polarization; Polyethylenes; Power transformers; Cable maintenance; Condition-based monitoring; Cross-linked polyethylene cables; High-voltage equipments; Insulation monitoring; Matching patterns; Polarization and depolarization currents; Simulation studies; Cable sheathing